The good dinosaur - Unknown Author (Parragon books, 2015)
"The Good Dinosaur" tells the story of Arlo, a young, fearful Apatosaurus, who gets separated from his family and embarks on a journey home. Along the way, he befriends a human boy named Spot and together they face challenges and learn to confront their fears in a prehistoric world where dinosaurs never went extinct. Arlo's journey is not just about finding his way back to his family, but also about personal growth and discovering his own bravery.